2018
DOI: 10.5897/ajest2018.2564
|View full text |Cite
|
Sign up to set email alerts
|

Comparative experimental study of performance degradation of amorphous silicon and crystalline silicon in outdoor exposed in Cologne

Abstract: The photovoltaic (PV) lifetime and the return-on-investment for local PV system installation rely on long-term device performance. Understanding the efficient degradation behavior under a given set of environmental conditions is, therefore, a primary goal for experimental research and economic analysis. The modules were characterized with measurement of their I-V features under similar outdoor condition. Moreover, measurement of different meteorological parameters like humidity and temperature is done from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…By means of comparison, studies conducted on outdoor exposed a-Si PV modules exhibited approximately 1.76-2.21 %/year performance loss [15]. However, it has been reported that RDa values are of 20.4 % in Malaysia and 18.8 % in Australia and Spain.…”
Section: Analytical Calculations Of Degradation Ratesmentioning
confidence: 99%
“…By means of comparison, studies conducted on outdoor exposed a-Si PV modules exhibited approximately 1.76-2.21 %/year performance loss [15]. However, it has been reported that RDa values are of 20.4 % in Malaysia and 18.8 % in Australia and Spain.…”
Section: Analytical Calculations Of Degradation Ratesmentioning
confidence: 99%